Effect of Detoxified Nano Sulfur Supplementation on the Growth, Nutrient Digestibility, Meat Quality, Excreta Microbes, Gas Emissions, and Blood Profiles of Broilers - Md Raihanul Hoque; Insun Park; Seyoung Mun; In Ho Kim (The Journal of Poultry Science, 2022)
A 35-day experiment was conducted to evaluate the effects of the supplementation of mineral detoxified sulfur dispersion ((DSD); Patent No.: 10-1997773) on the growth performance, meat quality, excreta microbiota, gas emissions, nutrient digestibility, and blood profiles of broilers. In total, 720 one-day-old ROSS 308 broilers, with an initial body weight of 41.9±0.8 g, were divided into two (2) treatment groups with 20 replicate pens/groups composed of 18 birds per pen. Treatments consisted of 1) CON (the control), normal drinking water and 2) TRT (the treatment group), CON+0.001% DSD (1000:1 dilution ratio). Average daily feed intake (ADFI) and feed conversion ratio (FCR) increased in the TRT group (P<0.05) between days 1 to 7 and days 7 to 21 of the experimental period. Similarly, body weight gain (BWG) showed a significant increase (P<0.05) in the DSD-supplemented group throughout in the length of the experiment. With regard to meat quality, redness (a*) was higher, while drip loss was lower, on the 7th day in the DSD group. Furthermore, DSD supplementation increased (P<0.05) Lactobacillus excreta but decreased E. coli concentrations in the TRT group compared to the CON group. Notably, nutrient digestibility, excreta gas emission, and blood profiles did not show any significant differences (P>0.05). DSD supplementation, administered through drinking water, has a positive impact on the growth performance, meat quality, and excreta microbiota of broiler chickens.